Closing the yield gap of soybean (Glycine max (L.) Merril) in southern Africa: a case of Malawi, Zambia, and Mozambique - Omondi, J.O.; Mkuhlani, S.; Mugo, J.; Chibeba, A.M.; Chiduwa, M.S.; Chigeza, G.; Boahen, S.; Masikati, Patricia; Nyagumbo, I. (Frontiers Media, 2023)
Introduction: Smallholder farmers in Sub-Saharan Africa (SSA) are increasingly producing soybean for food, feed, cash, and soil fertility improvement. Yet, the difference between the smallholder farmers’ yield and either the attainable in research fields or the potential from crop models is wide. Reasons for the yield gap include low to nonapplication of appropriate fertilizers and inoculants, late planting, low plant populations, recycling seeds, etc.